2000
DOI: 10.1046/j.1365-2591.1999.00297.x
|View full text |Cite
|
Sign up to set email alerts
|

Endodontic retreatment decisions: no consensus

Abstract: No clear consensus occurred amongst and within dental schools concerning the clinical management of the 14 cases. The lack of consensus amongst schools seems to be due mainly to chance or uncertainty, but can be partly explained by the 'school effect'.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
30
1
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 25 publications
(53 reference statements)
10
30
1
3
Order By: Relevance
“…Furthermore, in this study, 42.7% of the teeth were from male subjects, but there was no difference in the final outcome between the male and female groups. This lower rate has been confirmed in other studies as well [5,[18][19][20].…”
Section: Resultssupporting
confidence: 82%
“…Furthermore, in this study, 42.7% of the teeth were from male subjects, but there was no difference in the final outcome between the male and female groups. This lower rate has been confirmed in other studies as well [5,[18][19][20].…”
Section: Resultssupporting
confidence: 82%
“…Patients usually tend to choose treatment procedures consistent with the clinician's recommendation (18). However, it appears that the recommendations are often subjective and inconsistent, and there is a lack of consensus among dental professionals when making decisions related to retreatment or endodontic surgery (19)(20)(21)(22).…”
mentioning
confidence: 99%
“…In a study on endodontic retreatment decisions, Aryanpour et al [27] reported that the main source of variation among dental students, endodontic staff members and instructors in 10 European dental schools was what they called the 'school effect'. In our study, the school effect became manifest as participants who had had their undergraduate dental education in Eastern Europe or in the Middle East showed the highest CRT when it was associated with recurrent caries, whereas participants who had had their undergraduate training in North America or Asia had the lowest CRT.…”
Section: Discussionmentioning
confidence: 99%